Isolation and Antifungal Susceptibility of Candida spp. from Pediatric Patients - Bahi, Mohammed Salah; Mustafa Shekhany, Khattab Ahmed (Kurdistan Journal of Applied Research, 2023)
Candida species are considered the most common opportunistic human fungal pathogen due to the presence of various virulence factors, including its ability to form a biofilm that aids in oral candidiasis. Pediatric patients are more susceptible to oral candidiasis than healthy pediatric because of the factors that encourage Candida oral carriage. This current study aims to isolate, evaluated the antifungal effect on Candida spp. and participated in oral candidiasis of pediatric patients in Sulaymaniyah and Kirkuk city.  The study was performed from September 2021 to February 2022 on two groups of pediatrics which including pediatric patients (n=160) and healthy pediatric (n=50) as a control group. Oral swabs were obtained from 210 participants in the Kurdistan Region of Iraq at the Pediatric teaching hospital of the Sulaymaneyah and Kirkuk governorates. To culture the swabs, Sabouraud dextrose agar (SDA) medium was used. HiCrome™ Candida Differential agar used to identify Candida isolated, then depending on the internal transcribed spacer (ITS) region using confirmed polymerase chain reaction. Antifungal sensitivity was done for all C. albicans and non-albicans isolates using five common antifungal disks. Among of the 160 sample of pediatric patient 62 (38.8%) positive for Candida spp. which it is including 17 (27.4 %) and 26 (41.9%), 19 (30.6%) breast feeding, bottle feeding and mixing respectively. While within 50 samples of control group 13 (26%) were positive for Candida spp. which including 2 (15.4%), 9(69.2%), 2(15.4%) of same respectively feeding types. Regarding to the antifungal susceptibility the results showed that C. albicans had higher resistance rates against itraconazole, ketoconazole, and clotrimazole than the non-albicans Candida species However, highly resistant rate were detected in Itraconazole and Ketoconazole with 23.7% and 54.4% respectively, for all Candida species. The Current study concluded that oral candidiasis was more predominant in pediatric patients in compare to healthy pediatric also, and C. albicans is the most prevalent etiologic agent. However, higher rate of sensitivity were detected between Candida species for nystatin, which may suggest as the main treatment for oral Candida infections.